Quality of Work Life and its Relationship with Teaching Self-Efficacy Beliefs of Teachers in the Sultanate of Oman - Albuloshi, Maryam; Aldhafri, Said (Jordan Journal of Educational Sciences, 2019)
The present study aimed to predict teaching self-efficacy beliefs through work life quality of teachers in the Sultanate of Oman. The study also examined the differences between males and females in the teaching self-efficacy beliefs and in the dimensions of work life quality. The study adopted the descriptive predictive method where 1233 middle math teachers responded to two questionnaires measuring their efficacy beliefs and work life quality. The results of the study revealed that teachers have high levels of teaching self-efficacy beliefs and work life quality. There were statistically significant gender differences in efficacy beliefs and the dimensions of work life quality, favoring female teachers. The study found that gender contributes to the prediction of teaching self-efficacy beliefs by 3.7%. The model containing gender and the dimensions of work life quality explain 33.8% of the variance in efficacy beliefs.